2006
DOI: 10.1097/01.cco.0000198976.43992.14
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical carcinoma

Abstract: Pre-operative diagnostic advances in positron emission scanning are emerging as promising modalities for confirmation of malignancy of indeterminate adrenal masses. No significant advances in the treatment of adrenocortical carcinoma have been developed. Surgery remains the mainstay for primary and recurrent disease, including select patients with isolated liver metastases. Mitotane has remained the preferred adjuvant treatment agent, showing modest effect in patients with unresectable, residual or metastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
1
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 36 publications
1
69
1
17
Order By: Relevance
“…Adrenocortical carcinoma (ACC) is a rare and aggressive endocrine tumor showing an annual incidence of 0.5-2 cases/million population (1,2). Surgery is the mainstay of therapy and complete surgical removal of ACC is the most important prognostic factor for longterm survival together with stage.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenocortical carcinoma (ACC) is a rare and aggressive endocrine tumor showing an annual incidence of 0.5-2 cases/million population (1,2). Surgery is the mainstay of therapy and complete surgical removal of ACC is the most important prognostic factor for longterm survival together with stage.…”
Section: Introductionmentioning
confidence: 99%
“…The female:male ratio in this small sample size was 1:1. The majority of studies have demonstrated that women are more susceptible to the disease (1,28). Based on the collected data, there appear to be no significant differences in morbidity rates between male and female patients (Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…Adrenal sarcomatoid carcinomas are more likely to occur in the kidney or bladder, rather than the adrenal glands (17). These carcinomas may be classified as either functional or nonfunctional tumors (1). Patients with functional tumors may present with symptoms caused by excessive hormones, including the following: i) Cushing's syndrome; ii) severe hypertension; iii) male feminization or iv) female masculinization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations